A szlovákiai magyar kisebbség oktatási intézményrendszere : 1990-2004 - Jobbágy, István (Közép-Európai Közlemények, 2011)
In my work, we would like to evaluate the minority educational system of the ethnic Hungarians in Slovakia (1990–2004). At first, we will illuminate the structural problems of the elementary and secondary school system. According to the official statistics, in one hand, the Hungarian children are over represented in elementary school system, in the other hand, the proportion of ethnic Hungarian pupils in secondary school system is lower than the proportion in their age-group. The both mentioned phenomena can be explained by the relatively high proportion of Roma children in Hungarian educational system. However, there are other explanations (migration), which need more research. The main problem of the secondary school system: there are not enough professions in the offer of secondary schools in Hungarian language. That is why the ethnic Hungarian pupils are forced to learn in Slovak language classes. In the higher education, we can evaluate a positive political and institutional process, which ended in the foundation (2003) of the Selye University in Komárno. This university was the first state founded institution from 1918, which served the educational demands of the Hungarian ethnic minority in Slovakia.